2022
DOI: 10.1073/pnas.2121058119
|View full text |Cite
|
Sign up to set email alerts
|

RALF1 peptide triggers biphasic root growth inhibition upstream of auxin biosynthesis

Abstract: Plant cell growth responds rapidly to various stimuli, adapting architecture to environmental changes. Two major endogenous signals regulating growth are the phytohormone auxin and the secreted peptides rapid alkalinization factors (RALFs). Both trigger very rapid cellular responses and also exert long-term effects [Du et al., Annu. Rev. Plant Biol. 71, 379–402 (2020); Blackburn et al., Plant Physiol. 182, 1657–1666 (2020)]. However, the way, in which these disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
(105 reference statements)
0
24
0
Order By: Relevance
“…Its homologous gene in Arabidopsis was identified to contain a single nucleotide polymorphism site that was associated with phosphate use efficiency ( El-Soda et al , 2019 ). Chr7g0219691 encodes a feronia receptor-like kinase which regulates root elongation and responds to stresses ( Gigli-Bisceglia et al , 2022 ; Li et al , 2022 ). Moreover, this protein family regulates root microbiome regulation to alleviate phosphate starvation ( Tang et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its homologous gene in Arabidopsis was identified to contain a single nucleotide polymorphism site that was associated with phosphate use efficiency ( El-Soda et al , 2019 ). Chr7g0219691 encodes a feronia receptor-like kinase which regulates root elongation and responds to stresses ( Gigli-Bisceglia et al , 2022 ; Li et al , 2022 ). Moreover, this protein family regulates root microbiome regulation to alleviate phosphate starvation ( Tang et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, auxin-responsive genes were significantly repressed in gametophores, suggesting that attenuation of the auxin signal correlates with the transition to the reproductive phase in M. polymorpha (Flores-Sandoval et al, 2018). Additionally, recent studies showed that RALF1-FER inhibited root growth by induction of auxin biosynthesis in A. thaliana (Li et al, 2022), suggesting crosstalk between signaling peptides and phytohormones (Oh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the GhRALF1 transcription peaks appear to coincide with fiber cell elongation velocity peaks as well as apoplastic pH troughs, probably due to a temporal delay between transcription and physiological consequences as the peptides need time to be translated, secreted, and transduced. Another hypothesis is that GhRALF1 might in vivo promote fiber cell elongation, although a recent study also showed that RALF1 of Arabidopsis also inhibits cell growth in vivo [51]. Whether GhRALF1 promotes or inhibits the growth of cotton fiber cells in vivo remains to be elucidated by further studies.…”
Section: The Rhythmic Growth Regulation Of Fiber Cellsmentioning
confidence: 99%